The Role of Economic Education in Shaping Future Expectations Family Against Education - Rizky Mery Octavianna Lubis; Yusuf Pathuansyah; Makhrani; Abdelina (Yayasan Perguruan Kampus, 2024)
Family is the first place for children to get an education. Person parents act as educators in the family so that their daily attitude and actions days provide a stimulus to the child’s behaviour. Economic education in a family environment given by parents provides understanding and application of economic concept for children. The existence of financial education in the family is expected to be able to improve the family economy. This study contains how economic education is crucial to be taught and instilled in children to become individuals who behave economically in a rational, independent, and care for others. The research method used is the research method qualitative descriptive in a literature study with data sources derived from books or existing literature. This study indicates that attitudes and the behaviour that the child forms will influence their mindset deeply arrange and design its future.